Vibration isolation effects of barriers filled with ceramsite and Sand: Full-scale model test and numerical investigation. (25th July 2022) - Xi, Zhang; Weili, Luo; Benhai, Lin; Jiaofen, Qin; Cheng, Liao
Highlights: The ceramsite or the ceramsite-sand mix is first introduced as an in-filled material for wave barriers in mitigating railway-induced vibrations. A full-scale model test is conducted for studying the vibration isolation effects of the wave barriers in a continuous or non-continuous form. A 3D finite element analysis is conducted for a parametric study in terms of the contour map of the wavefield, the Arias intensity, the influence of different depths, and the different ceramic ratios. Abstract: Barrier is an effective vibration isolation measure to reduce railway-induced vibrations. However, the full-scale model test is seldom conducted. In this paper, the ceramsite or the ceramsite-sand mix is first introduced as an in-filled material for wave barriers in mitigating railway-induced vibrations. A full-scale model test and a 3D finite element model with a perfectly matched layer as the absorbing boundary are used for studying the vibration isolation effects of the wave barriers in a continuous or non-continuous form. Before the test, the dynamic parameters of soil in the test site are obtained by the MASW test. The transfer function and the insertion loss due to the barriers at the fixed observation points have been experimentally investigated. Subsequently, the contour map of the wavefield, the Arias intensity, the influence of different depths, and the different ceramic ratios on the vibration isolation effect are examined by the numerical model. Results show the promising screening effectiveness of the ceramsite-sand mix barrier.